Distortion in Electrodynamic Loudspeakers Caused by Force Factor Variations - Mehran ERZA; Guy LEMARQUAND; Valerie LEMARQUAND (Archives of Acoustics)
The non linearities in the motor of an electrodynamic loudspeaker are still a discussed topic. This paper studies the influence of the force factor variation with the coil displacement on the harmonic and inter-modulation distortions. The real variation is described at least by a linear and a quadratic term. The effect of each term is studied separately, as they don’t influence the same kind of frequencies, harmonics or inter-modulation. Both terms considered together result in enhanced effects. The dissymmetry of the Bl variation with regard to the coil centered position has also peculiar effects. This paper presents the method developed to calculate the power of each harmonic and inter-modulation frequency. This allows to compare the obtained values and thus the induced nonlinearities.